Combination of a CD26 Inhibitor, G-CSF, and Short-term Immunosuppressants Modulates Allotransplant Survival and Immunoregulation in a Rodent Hindlimb Allotransplant Model. Issue 6 (June 2021) - Chen, Chien-Chang; Chen, Rong-Fu; Wang, Yu-Chi; Li, Yun-Ting; Chuang, Jiin-Haur; Kuo, Yur-Ren
Abstract : Background: Recent studies have demonstrated that inhibition of CD26 potentiates stromal cell–derived factor-1α (SDF-1α), promotes tissue regeneration, and suppresses the rejection of organ transplants. This study investigated whether the combination of a CD26 inhibitor (CD26i) with granulocyte colony-stimulating factor (G-CSF) and short-term immunosuppressants modulates vascularized composite tissue allotransplant survival in a rodent orthotopic hindlimb allotransplant model. Methods: The hindlimb allotransplantation from Brown-Norway to Lewis rats was divided into 4 groups. Group 1 (controls) did not receive any treatment. Group 2 was treated with short-term antilymphocyte serum (ALS) and cyclosporine-A (CsA). Group 3 was administrated CD26i and G-CSF. Group 4 received a combination of CD26i/G-CSF/ALS/CsA. Each subgroup comprised 10 rats. Peripheral blood and sampling of transplanted tissues were collected for immunological and histological analysis. Results: The results revealed that allotransplant survival was found to be significantly prolonged in group 4 with CD26i/G-CSF/ALS/CsA treatment compared with those in the other groups. The interleukin-10 and transforming growth factor-βl levels, the percentage of CD4 + /CD25 + /FoxP3 + T cells, as well as the levels of SDF-1α expressions were significantly increased in group 4 compared with those in the other groups. Group 4 revealed a statistical increase in the percentage of donor cells (RT1 n ) expression in the recipient peripheral blood, and the mixed lymphocyte reaction showed hyporesponsiveness of the T cells to donor alloantigens. Conclusion: The combination of CD26i/G-CSF and short-term immunosuppressants prolongs allotransplant survival by inducing immunoregulatory effects and enhancing the percentage of SDF-1α expression. This immunomodulatory approach has great potential as a strategy to increase vascularized composite allotransplantation survival.